A novel branch current flow-based construction of microgrids - Kavitha Sivakumar; Jayashree R; Karthikeyan Danasagaran (Institute of Advanced Engineering and Science, 2021)
An efficient procedure for defining the boundaries of microgrids in smart distribution systems during distributed generation expansion planning becomes an important consideration in constructing smart grids. A novel approach named